COMPARISON BETWEEN INCISAL AND OCCLUSAL TOOTH WEAR IN PATIENTS UNDERGOING DENTAL TREATMENT - K, Sathvika; Sasanka L, Keerthi; L. , Leelavathi (International Journal of Psychosocial Rehabilitation, 2020)
Tooth wear (TW) is a progressive condition that affects our dentition throughout life. It includes attrition, abrasion, erosion, and abfraction. Since attrition is the most prevalent type of TW, we have attempted to compare its incidence occlusally (in posterior teeth) and incisally (in anterior teeth), hoping that the results may help recruit appropriate methods of prophylaxis to decrease the incidence of TW in patients undergoing dental treatments. A retrospective cross-sectional study was conducted using 86,000 patient records from Saveetha Dental College between June 2019 and April 2020. Patients with established records of attrition in their dental statuses were selected from the ages of 40 to 70 years. A Microsoft Excel data spreadsheet was used to collect data and was later exported to SPSS for Windows. Out of a total of 57 patients, 77.2% were males and 22.8% were females, highlighting a male predilection for TW. The highest incidence, at 47.4%, was seen both incisally and occlusally - that is, in patients having attrition in both sites. It was followed by patients having attrition only in the occlusal aspect (31.6%) and lastly patients with only incisal TW (21.1%). On cross-tabulating gender and the type of TW, we inferred that in males it was most common to experience TW both incisally and occlusally and that they experienced incisal tooth wear the least. In females, it was suggested that the most amount of TW was incident occlusally and least of all, incisally. Once lost, tooth structure cannot be naturally replaced. Thus, its prevention is imperative. Identifying a pattern in its incidence is a great step forward in terms of improving existing prophylactic measures. Thus, further studies must be carried out to overcome our limitations and to confirm our findings.